(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Importance. Thyroid hormones from the mother are essential for normal fetal development, like brain growth. There are metabolic needs in pregnancy, producing physiological adjustments inside the thyroid that bring about increased manufacturing of hormones. Placental iodothyronine deiodinases have a careful control of the passage of these hormones to the fetus. Both higher and lower levels of thyroid hormone exert teratogenic effects. For this reason, right detection and management of thyroid issues in pregnancy are vital to save you unfavorable outcomes in the maternal, fetal and new child [1]. The Objective is to highlight the importance of thyroid disorders during pregnancy and its management. The main goal of prenatal screening and diagnosis of thyroid related pathophysiology changes that occur during pregnancy.